Revision and cladistic analysis of the Southeast Asian leaf-dwelling spider genus Calapnita Simon (Araneae, Pholcidae) - Huber, Bernhard A. (Zootaxa, 2017)
The Southeast Asian pholcid genus Calapnita Simon, 1892 is revised, with descriptions of 17 new species, five of them in the phyllicola group (Borneo: C. lehi, C. kubah, C. bidayuh, C. bankirai; Malay Peninsula, Sumatra, Java: C. anai), 12 in the vermiformis group (Borneo: C. bario, C. bariengi, C. magaseng, C. dayak, C. lawangan, C. loksado; Sulawesi: C. bugis; Philippines: C. bohol, C. dinagat, C. mae, C. nunezae, C. maragusan). New records are listed for six of the eight previously described species. A morphological cladistic analysis supports the monophyly of Calapnita and of its two previously proposed species groups and presents several new phylogenetically informative characters. New data are presented about ultrastructure and natural history (web, egg-sac, egg parasitism).